High-Throughput Alloy Development Using Advanced Characterization Techniques During Directed Energy Deposition Additive Manufacturing - Sommer, Niklas; Bauer, André; Kahlmeyer, Martin; Wegener, Thomas; Degener, Sebastian; Liehr, Alexander; Bolender, Artjom; Vollmer, Malte; Holz, Hendrik; Zeiler, Stefan; Merle, Benoit; Niendorf, Thomas; et al. (Advanced Engineering Materials, 2023)
In laser-based direct energy deposition (DED-LB) additive manufacturing (AM), wire or powder materials are melted by a high-power laser beam. Process-specific characteristics enable robust in situ fabrication of compositionally graded materials, e.g., through an adaption of powder mass flow from independent hoppers. Based on the high flexibility of this approach, pathways toward multimaterial AM have been unlocked. Obviously, such characteristics enable high-throughput alloy development. However, rapid alloy development demands substantial characterization efforts to assess phase and microstructural evolution. So far, property analysis is considered as the limiting factor for these high-throughput approaches. Herein, the use of high-brilliance X-Ray analysis and subsequent micropillar compression testing are introduced to tackle these challenges. As a proof of concept, their application to a compositionally graded material made from AISI 316L stainless steel and a CoCrMo alloy is presented. The results obtained reveal that X-Ray analysis can be exploited to evaluate process robustness, chemical characteristics, and phase composition within the gradient regions. Moreover, the use of micropillar compression testing provides spatially resolved insights into the mechanical properties of the gradient regions. The combination of both characterization techniques eventually opens pathways toward a robust and time-efficient alloy development using powder-fed DED-LB (DED-LB/P).
CRIS-Team Scopus Importer:2023-04-28
Keywords: additive manufacturing; alloy development; direct energy deposition; in situ characterization